The role of local biodiversity in meeting nutritional requirements for complementary foods of infants and young children, Southern Benin - Ntandou-Bouzitou, Gervais D.; Termote, Céline; Waliou, A.; Mutanen, M. (FoodAfrica, 2016)
The mothers/care-givers, and the communities in general, will benefit from locally adapted information and knowledge on how to improve diets making the best use of the locally available biodiversity. Better knowledge and improved complementary feeding practices will contribute to better nutritional status of children and thus healthier and more productive communities.